Outcome of Community-Acquired Staphylococcus aureus Bacteraemia in Patients with Diabetes: A Historical Population-Based Cohort Study - Smit, Jesper (PLoS One, 2016)
BACKGROUND: Patients with diabetes (DM) experience increased risk of Staphylococcus aureus bacteraemia (SAB), but the prognostic impact of diabetes in patients with SAB remain unclear. Therefore, we investigated 30-day all-cause mortality in patients with and without DM. METHODS: Population-based medical databases were used to conduct a cohort study of all adult patients with community-acquired SAB in Northern Denmark, 2000–2011. Using Cox proportional hazards regression, we computed hazard ratios as estimates of 30-day mortality rate ratios (MRRs) among patients with and without DM. We further investigated whether the prognostic impact of DM differed among patients with and without recent preadmission healthcare contacts (within 30 days of the current hospitalization) and by age, sex, marital status, level of comorbidity, and DM-related characteristics (e.g., duration of DM and presence of DM complications). RESULTS: Among 2638 SAB patients, 713 (27.0%) had DM. Thirty-day cumulative mortality was 25.8% in patients with DM and 24.3% in patients without DM, for an adjusted MRR (aMRR) of 1.01 (95% confidence interval (CI), 0.84–1.20). In analyses with and without recent healthcare contacts, the corresponding aMRRs were 0.84 (95% CI, 0.62–1.14) and 1.13 (95% CI, 0.91–1.41), respectively. Compared to patients without DM, the aMRR was 0.94 (95% CI, 0.74–1.20) for male patients with DM and 1.13 (95% CI, 0.87–1.47) for female patients with DM. The prognostic influence of DM on mortality did not differ notably with age, level of comorbidity, or characteristics of patients with DM. CONCLUSION: Patients with DM and community-acquired SAB did not experience higher 30-day mortality than patients without DM.